2017
DOI: 10.1111/cup.12973
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 and PD‐L1 in neoplastic cells and the tumor microenvironment of Merkel cell carcinoma

Abstract: Our data demonstrate that PD-L1 expression occurs in tumor and immune cells, in areas in which they are close in contact. Interferon seems to play a role in this interaction. We postulate that PD-L1(+)/CD33(+) cells shield the tumor against attacking PD-1(+) immune cells. Therefore, next to anti-PD-1/PD-L1 antibodies, blockade of CD33 seems to be a promising therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
4
22
0
1
Order By: Relevance
“…These results confirm previously published data [ 10 15 ] and extend these observations to the identification of specific T-cell, macrophage and B-cell subsets whose presence is associated with MCPyV. Our data concerning PDL1 expression are largely consistent with those recently published by Walsh and coworkers [ 11 ], i.e., PDL1 is mainly expressed by peritumoral macrophages rather than neoplastic cells [ 13 , 23 ]: in our series, PDL1 expression by neoplastic cells was observed in just 22/179 (12%) cases, a slightly lower proportion than that found by Wehkamp et al and Benigni et al [ 24 , 25 ]. Our results are basically consistent with those of Miller et al, who showed that MCPyV-positive tumors had a strikingly more clonal intratumoral TCR repertoire than MCPyV-negative tumors [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results confirm previously published data [ 10 15 ] and extend these observations to the identification of specific T-cell, macrophage and B-cell subsets whose presence is associated with MCPyV. Our data concerning PDL1 expression are largely consistent with those recently published by Walsh and coworkers [ 11 ], i.e., PDL1 is mainly expressed by peritumoral macrophages rather than neoplastic cells [ 13 , 23 ]: in our series, PDL1 expression by neoplastic cells was observed in just 22/179 (12%) cases, a slightly lower proportion than that found by Wehkamp et al and Benigni et al [ 24 , 25 ]. Our results are basically consistent with those of Miller et al, who showed that MCPyV-positive tumors had a strikingly more clonal intratumoral TCR repertoire than MCPyV-negative tumors [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Immunohistochemical staining of 8 VN-MCC and 34 VP-MCC showed that none of the VN tumors expressed PD-L1, while 50% of the VP-MCCs were positive for PD-L1 [ 199 ]. Another study on 14 MCC (6 VN and 8 VP) reported that 1 VN-MCC had few (1%) PD-L1 positive tumors cells, whereas 7 of the VP-MCC were PD-L1 positive with 2–7.5% of the cells expressing PD-L1 [ 200 ]. It is not known whether MCPyV can affect the expression of PD-L1, but upregulation of PD-L1 has been observed in persistent infection with the oncoviruses hepatitis B and C [ 201 ].…”
Section: Immune Evasion Of Vp-mccmentioning
confidence: 99%
“…Previous work has suggested that proinflammatory cytokine release by T cells is enhanced with PD-1 axis blockade [ 15 ]. Moreover, patients with untreated CLL and MCC are known to have an expanded myeloid derived suppressor cell (MDSC) compartment [ 16 ] and MDSC compartment at the tumor microenvironment interface [ 17 ], respectively. RT may have rapidly depleted MDSCs and allowed for unchecked elaboration of pro-inflammatory cytokines [ 18 ].…”
Section: Discussionmentioning
confidence: 99%